(untitled) (Journal of the College of Basic Education, 2024)
In this thesis, the researcher has relied on a descriptive and analytical approach, the aim of which is to clarify the issue of religious guardianship. The importance and fruit of this research on the subject of religious guardianship in the Holy Qur’an is highlighted through rational evidence of formative guardianship, legislative guardianship, and transmissional evidence of religious guardianship, which are: the Qur’an and the narrations: the religious guardianship of the Messenger of God. And the imams.